Antifouling paint composition
By introducing silane ester polymers and acrylic polymers of specific structural units into the anti-pollution coating, combining copper oxides and monocarboxylic acid compounds, the crack resistance and adhesion of the anti-pollution coating under dynamic conditions is solved, and high stability and good anti-fouling properties are achieved, which is suitable for repairing damaged coatings.
Patent Information
- Application Number
- JP2021047536
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-03-22
AI Technical Summary
The existing anti-pollution coatings have insufficient anti-fouling properties and crack resistance under dynamic conditions, and have poor long-term storage stability, making it difficult to form good adhesion to damaged coatings.
Anti-fouling coating compositions containing silane ester polymers, acrylic polymers and copper oxides with specific structural units are used, combined with monocarboxylic acid compounds such as rosin to improve the crack resistance, adhesion and dynamic pollution resistance of the coating, and to improve storage stability by controlling component ratios and process optimization.
A coating with excellent crack resistance, adhesion and dynamic stain resistance is formed, which significantly improves the storage stability of the coating and is suitable for the repair and maintenance of damaged coatings.
Smart Images

Figure 0007628039000001 
Figure 0007628039000002 
Figure 0007628039000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an antifouling coating composition, an antifouling coating film, a substrate with an antifouling coating film, and a method for producing a substrate with an antifouling coating film. [Background technology]
[0002] A wide variety of aquatic organisms are likely to attach to the surfaces of substrates (ships, underwater structures, fishing nets, seawater supply and drainage pipes for factories, etc.) that are exposed to water (oceans, rivers, lakes, etc.) for long periods of time in the natural environment. When aquatic organisms attach to the surface of the substrate, it can cause a variety of problems, including a loss of appearance and a decrease in the vessel's speed and an increase in fuel consumption, due to an increase in resistance caused by the water flow when the substrate is a ship. When the substrate is an underwater structure, the anticorrosive coating applied to the substrate surface can be damaged, resulting in damage such as a decrease in strength and functionality, and a significant shortening of the lifespan. When the substrate is a fishing net such as an aquaculture net or a fixed net, the meshes can be clogged by aquatic organisms, causing serious problems such as the death of cultured and caught organisms due to lack of oxygen. When aquatic organisms attach to and multiply in seawater supply and drainage pipes in factories and thermal and nuclear power plants, it can cause blockage of the pipes and a decrease in the flow rate.
[0003] In order to prevent the adhesion of aquatic organisms that cause such problems, an antifouling coating film is usually formed by applying an antifouling coating material to the surface of a substrate. Among these antifouling coating materials, hydrolysis-type antifouling coating materials are widely used because of their advantages such as excellent antifouling performance, and as one of them, antifouling coating materials containing silyl ester polymers have been developed.
[0004] Patent Document 1 describes an antifouling coating composition containing a silyl ester copolymer containing triisopropylsilyl methacrylate and a hydrophilic (meth)acrylate comonomer, and medetomidine. Patent Document 2 describes an antifouling coating composition in which a copolymer containing a structural unit derived from styrene and a structural unit derived from glycidyl (meth)acrylate is blended with an antifouling coating containing a silyl ester polymer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2019-535868 [Patent Document 2] International Publication No. 2014 / 175246 Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 discloses that the antifouling coating composition can form a coating film having cracking resistance and excellent antifouling properties, particularly excellent barnacle adhesion inhibition properties. However, in the examples of the document, although barnacle resistance is evaluated by a static immersion test as antifouling performance, dynamic antifouling properties are unknown. Furthermore, according to the study by the present inventors, it was found that it is difficult to form an antifouling coating film formed from an antifouling paint composition containing medetomidine that is excellent in all of crack resistance, adhesion to a previous antifouling coating film that has been immersed in seawater or the like and deteriorated (hereinafter also simply referred to as a deteriorated coating film), and dynamic antifouling properties. Furthermore, it was found that the antifouling coating composition has room for improvement in terms of long-term storage stability.
[0007] An object of the present invention is to provide an antifouling coating composition containing a silyl ester polymer and medetomidine, which is capable of forming an antifouling coating film excellent in crack resistance, adhesion to deteriorated coating films, and dynamic antifouling properties, and which has excellent storage stability. [Means for solving the problem]
[0008] The present inventors have conducted intensive research to solve the above problems and have found that the antifouling coating composition described below can solve the above problems. That is, the present invention relates to the following [1] to
[10] .
[0009] [1] An antifouling coating composition comprising a silyl ester polymer (A) having a structural unit (a-1) derived from a polymerizable monomer (a1) represented by formula (a1), an acrylic polymer (B) having a structural unit (b-1) derived from glycidyl (meth)acrylate, medetomidine (C), and cuprous oxide (D), An antifouling coating composition, wherein the content of the cuprous oxide (D) is more than 0 mass % and not more than 55 mass % of the solid content of the antifouling coating composition. R 1 -CH=C(CH3)-COO-(SiR 2 R 3 O) n -SiR 4 R 5 R 6 …(a1) [In formula (a1), R 2 ~R 6 are each independently a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom. n is an integer of 0 or 1 or more. R 1 is a hydrogen atom or R 7 A group represented by -OC(=O)-, R 7 represents a hydrogen atom, a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom, or R 8 R 9 R 10 is a silyl group represented by Si-, 8 , R 9 and R 10 each independently represents a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom.]
[0010] [2] The antifouling coating composition according to [1] above, further comprising a monocarboxylic acid compound (E). [3] The antifouling coating composition according to [2] above, wherein the monocarboxylic acid compound (E) is a rosin (E1).
[0011] [4] The antifouling coating composition according to [3] above, wherein a mass ratio of the rosin (E1) to the total of the silyl ester polymer (A) and the acrylic polymer (B) (total mass of polymer (A) and polymer (B) / mass of rosin (E1)) is 0.7 to 4. [5] The antifouling coating composition according to any one of the above [1] to [4], further comprising talc, the talc content being 2 to 17 mass % of the solid content of the antifouling coating composition.
[0012] [6] The antifouling coating composition according to any one of [1] to [5] above, which is used for repairing a deteriorated antifouling coating film.
[0013] [7] An antifouling coating film formed from the antifouling coating composition according to any one of [1] to [6] above. [8] A substrate having an antifouling coating film, comprising a substrate and the antifouling coating film according to [7] provided on a surface of the substrate.
[0014] [9] The substrate having an antifouling coating film according to [8] above, wherein the substrate is at least one selected from ships, underwater structures, fishing equipment, and water supply and drainage pipes.
[10] A method for producing a substrate having an antifouling coating film, comprising a step of applying or impregnating a substrate with the antifouling coating composition according to any one of the above [1] to [6]. Effect of the Invention
[0015] According to the present invention, there is provided an antifouling coating composition containing a silyl ester polymer and medetomidine, which is capable of forming an antifouling coating film that is excellent in crack resistance, adhesion to deteriorated coating films, and dynamic antifouling properties, and which has excellent storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described in detail. Each of the components described in this specification may be used alone or in combination of two or more. The term "polymer" is used to include homopolymers and copolymers. "(Meth)acrylate" is a general term for acrylate and methacrylate. The same applies to the use of (meth)acrylic acid, etc.
[0017] "Structural unit derived from XX" means XX is A 1 A 2 C=CA 3 A 4 (C=C is a polymerizable carbon-carbon double bond, A 1 ~A 4 are atoms or groups bonded to carbon atoms), then, for example, the structural unit is represented by the following formula:
[0018] [ka]
[0019] [Antifouling paint composition] The antifouling coating composition of this embodiment (hereinafter also referred to as "composition (I)") contains a silyl ester polymer (A), an acrylic polymer (B), medetomidine (C), and cuprous oxide (D), each of which is explained below.
[0020] <Silyl ester polymer (A)> The silyl ester polymer (A) (hereinafter also referred to as "polymer (A)") has a structural unit (a-1) derived from a polymerizable monomer (a1) represented by formula (a1). R 1 -CH=C(CH3)-COO-(SiR 2 R 3 O) n -SiR 4 R 5 R 6 …(a1) Each symbol in formula (a1) is explained below. R 2 ~R 6are each independently a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom. Examples of this organic group include a linear or branched alkyl group, a cycloalkyl group, and an aryl group, in which a heteroatom such as an oxygen atom may be interposed between bonds between carbon atoms. From the viewpoint of easily obtaining a coating film with a good balance between crack resistance and long-term dynamic soil resistance due to moderate hydrolysis resistance, the organic group is preferably at least one selected from a linear or branched alkyl group having 1 to 8 carbon atoms and a phenyl group, and more preferably a branched alkyl group.
[0021] Examples of the straight-chain or branched alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a t-butyl group, a pentyl group, a hexyl group, and a 2-ethylhexyl group, and preferably an isopropyl group.
[0022] n is an integer of 0 or 1 or more, and is preferably 0. The upper limit of n may be 50, for example. R 1 is a hydrogen atom or R 7 R is a group represented by -OC(=O)-, and is preferably a hydrogen atom. 7 represents a hydrogen atom, a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom, or R 8 R 9 R 10 It is a silyl group represented by Si-. R 8 , R 9 and R 10 are each independently a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom. Specific examples of the monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom include those mentioned above.
[0023] As the polymerizable monomer (a1), trialkylsilyl methacrylate, alkyldiarylsilyl methacrylate and aryldialkylsilyl methacrylate are preferred, and trialkylsilyl methacrylate is more preferred. As the trialkylsilyl methacrylate, for example, trimethylsilyl methacrylate, triethylsilyl methacrylate, tripropylsilyl methacrylate, triisopropylsilyl methacrylate, tributylsilyl methacrylate, triisobutylsilyl methacrylate, tri-sec-butylsilyl methacrylate, tri-2-ethylhexylsilyl methacrylate, and butyldiisopropylsilyl methacrylate can be mentioned. In addition, as the polymerizable monomer (a1), a polymerizable monomer in which n is 2 or more in the above formula (a1), such as 1-methacryloyloxynonamethyltetrasiloxane, can also be mentioned. Among these, trialkylsilyl methacrylates having a branched alkyl group are preferred, and triisopropylsilyl methacrylate is particularly preferred, from the viewpoint of easily obtaining an antifouling coating film that has a well-balanced and excellent long-term dynamic antifouling property having crack resistance and moderate hydrolysis resistance.
[0024] The structural unit (a-1) may be of one type or of two or more types. The polymer (A) may further have a structural unit (a-2) derived from another ethylenically unsaturated monomer (hereinafter also referred to as "monomer (a2)").
[0025] An example of the monomer (a2) is a polymerizable monomer (a11) represented by the formula (a11). R 1 -CH=CH-COO-(SiR 2 R 3 O) n -SiR 4 R 5 R 6 …(a11) In formula (a11), R 1 ~R 6 and n have the same meaning as the same symbol in formula (a1).
[0026] Examples of the polymerizable monomer (a11) include trialkylsilyl acrylate, alkyldiarylsilyl acrylate, and aryldialkylsilyl acrylate. Examples of the trialkylsilyl acrylate include trimethylsilyl acrylate, triethylsilyl acrylate, tripropylsilyl acrylate, triisopropylsilyl acrylate, tributylsilyl acrylate, triisobutylsilyl acrylate, tri-sec-butylsilyl acrylate, tri-2-ethylhexylsilyl acrylate, and butyldiisopropylsilyl acrylate. Examples of the polymerizable monomer (a11) include polymerizable monomers in which n is 2 or more in the above formula (a11), such as 1-acryloyloxynonamethyltetrasiloxane.
[0027] From the viewpoint of the crack resistance (water resistance) of the antifouling coating film, it is preferable to use the polymerizable monomer (a1) represented by formula (a1) rather than the polymerizable monomer (a11) represented by formula (a11).
[0028] Examples of the monomer (a2) include (Meth)acrylic acid; (meth)acrylic acid esters (excluding the polymerizable monomers (a1) and (a11)), specifically, alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3,5,5-trimethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, and stearyl (meth)acrylate; alicyclic (meth)acrylates such as cyclohexyl (meth)acrylate; Aromatic ring-containing (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; alkoxyalkyl (meth)acrylates or aryloxyalkyl (meth)acrylates such as methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, methoxypropyl (meth)acrylate, ethoxypropyl (meth)acrylate, propoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, isobutoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; Glycol (meth)acrylates such as ethoxy-diethylene glycol (meth)acrylate, methoxy-triethylene glycol (meth)acrylate, and methoxy-dipropylene glycol (meth)acrylate; Vinyl monomers, specifically, vinyl acetate, isobutyl vinyl ether, styrene, vinyl toluene, (meth)acrylonitrile, vinyl propionate, and vinyl benzoate; Metal ester group-containing (meth)acrylates, specifically, zinc (meth)acrylate, zinc di(meth)acrylate, copper (meth)acrylate, copper di(meth)acrylate Other examples include:
[0029] Among the monomers (a2), alkyl (meth)acrylates, alicyclic (meth)acrylates, alkoxyalkyl (meth)acrylates and glycol-based (meth)acrylates are preferred, and alkyl (meth)acrylates and alkoxyalkyl (meth)acrylates are more preferred.
[0030] The structural unit (a-2) may be of one type or of two or more types. The proportion of the structural unit (a-1) in the polymer (A) is preferably 35 mass% or more, more preferably 40 mass% or more, even more preferably 45 mass% or more, and is preferably 80 mass% or less, more preferably 75 mass% or less, even more preferably 70 mass% or less.
[0031] The proportion of the structural unit (a-2) in the polymer (A) is preferably 20 mass% or more, more preferably 25 mass% or more, even more preferably 30 mass% or more, and is preferably 65 mass% or less, more preferably 60 mass% or less, even more preferably 55 mass% or less.
[0032] When the ratio of each structural unit is within the above range, the antifouling coating film formed from the composition (I) has a moderate hydrolysis property and tends to have excellent antifouling properties for a long time. The ratio of each structural unit can be determined by NMR (nuclear magnetic resonance spectroscopy), Pyro-GC / MS (pyrolysis gas chromatography / mass spectrometry), etc.
[0033] From the viewpoint of improving the crack resistance of the antifouling coating film formed from the composition (I), the weight average molecular weight (Mw) of the polymer (A) is preferably 3,000 or more, more preferably 10,000 or more, and preferably 70,000 or less, more preferably 50,000 or less. Mw can be determined by gel permeation chromatography (GPC) measurement or an equivalent method under the conditions employed in the examples described later. The polymer (A) can be used alone or in combination of two or more.
[0034] <Acrylic polymer (B)> Although a coating film containing hydrolyzable silyl ester polymer (A) and medetomidine (C) dissolves at a constant rate in seawater for a certain period of time from the beginning of immersion, the progress of hydrolysis inside the coating film reduces the water resistance of the coating film, and cracks and peeling may occur. To address this problem, by blending the silyl ester polymer (A) with the specific acrylic polymer (B) described below, it is possible to improve the crack resistance of the coating film while maintaining its dynamic antifouling properties.
[0035] The acrylic polymer (B) (hereinafter also referred to as "polymer (B)") has a structural unit (b-1) derived from glycidyl (meth)acrylate. The structural unit (b-1) contributes to improving the dynamic antifouling properties of the antifouling coating film formed from the composition (I) and the adhesion to deteriorated coating films.
[0036] The structural unit (b-1) may be of one type or two types. The proportion of the structural unit (b-1) in the acrylic polymer (B) is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 25% by mass or less, and particularly preferably 15% by mass or less. When the proportion of the structural unit (b-1) is equal to or more than the above lower limit, the dynamic antifouling property of the antifouling coating film and the adhesion to the deteriorated coating film are high, and when the antifouling coating composition contains a pigment described later, sufficient dispersibility of the pigment is obtained, which is preferable. When the proportion of the structural unit (b-1) is equal to or less than the above upper limit, the antifouling property is high, which is preferable. Furthermore, when the proportion of the structural unit (b-1) is in a particularly preferable range, the composition tends to have better storage stability. The acrylic polymer (B) preferably further has a structural unit (b-2) derived from an aromatic vinyl compound.
[0037] The structural unit (b-2) has a phenyl group, which is a hydrophobic functional group, and contributes to improving the crack resistance of the antifouling coating film formed from the composition (I), as well as the hardness, impact resistance, and abrasive cleanability of the coating film. The reason for the improved abrasive cleanability is not clear, but it is presumed that the structural unit (b-2) improves the hardness of the antifouling coating film formed and exerts physical abrasive cleanability against external forces such as frictional resistance in water.
[0038] Examples of aromatic vinyl compounds include styrene compounds such as styrene, methylstyrene, 2,4-dimethylstyrene, ethylstyrene, p-tert-butylstyrene, and monochlorostyrene, and among these, styrene is preferred.
[0039] The structural unit (b-2) may be of one type or of two or more types. The proportion of the structural unit (b-2) in the acrylic polymer (B) is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and is preferably 80% by mass or less, more preferably 75% by mass or less, even more preferably 70% by mass or less. When the proportion of the structural unit (b-2) is equal to or more than the lower limit, the crack resistance and impact resistance of the antifouling coating film are high, which is preferable. When the proportion of the structural unit (b-2) is equal to or less than the upper limit, the hydrophobicity of the antifouling coating film is not too high, and the hydrolysis of the polymer (A) is not hindered, so that the antifouling property is excellent.
[0040] The acrylic polymer (B) may further have a structural unit (b-3) derived from another ethylenically unsaturated monomer (hereinafter also referred to as "monomer (b3)"). Examples of the monomer (b3) include (Meth)acrylic acid; (Meth)acrylic acid esters (excluding glycidyl (meth)acrylate), specifically, alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3,5,5-trimethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, and stearyl (meth)acrylate; alicyclic (meth)acrylates such as cyclohexyl (meth)acrylate; Aromatic ring-containing (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; alkoxyalkyl (meth)acrylates or aryloxyalkyl (meth)acrylates such as methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, methoxypropyl (meth)acrylate, ethoxypropyl (meth)acrylate, propoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, isobutoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; Glycol (meth)acrylates such as ethoxy-diethylene glycol (meth)acrylate, methoxy-triethylene glycol (meth)acrylate, and methoxy-dipropylene glycol (meth)acrylate; Epoxy group-containing (meth)acrylates other than glycidyl (meth)acrylate; Polyfunctional (meth)acrylates, specifically, tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, di(trimethylolpropane)tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate; Vinyl monomers (excluding aromatic vinyl compounds), specifically, vinyl acetate, isobutyl vinyl ether, (meth)acrylonitrile, vinyl propionate, vinyl benzoate Examples include:
[0041] Among these, (meth)acrylic acid esters are preferred, alkyl (meth)acrylates are more preferred, and methyl (meth)acrylate and butyl (meth)acrylate are even more preferred.
[0042] The structural unit (b-3) may be of one type or of two or more types. By changing the type or amount of the structural unit (b-3), it is possible to adjust the viscosity and glass transition temperature of the acrylic polymer (B) and the hardness of the antifouling coating film.
[0043] The proportion of the structural unit (b-3) in the acrylic polymer (B) is preferably 89 mass % or less, more preferably 82 mass % or less, and even more preferably 75 mass % or less. The proportion of each structural unit can be determined by the same method as in the silyl ester polymer (A).
[0044] The weight average molecular weight (Mw) of the acrylic polymer (B) is preferably 2,000 or more, more preferably 5,000 or more, and preferably 50,000 or less, more preferably 30,000 or less, from the viewpoint of improving the crack resistance of the antifouling coating film formed from the composition (I). Mw can be determined by gel permeation chromatography (GPC) measurement or an equivalent method under the conditions employed in the examples described later. The acrylic polymer (B) may be used alone or in combination of two or more.
[0045] The content of the acrylic polymer (B) in the composition (I) is preferably 5 parts by mass or more, relative to 100 parts by mass of the silyl ester polymer (A), and from the viewpoint of further improving the crack resistance of the antifouling coating film and the adhesion to deteriorated coating films, it is more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, and is preferably 200 parts by mass or less, and from the viewpoint of further improving the dynamic antifouling properties of the antifouling coating film, it is more preferably 130 parts by mass or less, and even more preferably 110 parts by mass or less.
[0046] The total content of the silyl ester polymer (A) and the acrylic polymer (B) is preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 30% by mass or less, more preferably 25% by mass or less, based on 100% by mass of the total solid content of the composition (I). When the total content is within this range, an antifouling coating film having excellent crack resistance can be easily obtained.
[0047] The solid content in composition (I) is preferably 50% by mass or more, more preferably 60% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less.
[0048] In this specification, the solid content and its content of composition (I) are the heating residue (non-volatile content) and its content obtained by the following method or an equivalent method. Composition (I) is weighed out into a metal test dish of known mass and spread evenly on the bottom surface. It is heated in a hot air dryer at a temperature of 105 to 110°C for 3 hours to remove the volatile content. After removing it and cooling it to room temperature (e.g. 23°C), the mass of the obtained non-volatile content (heating residue) is measured, and the content of the solid content (heating residue) is calculated from the following formula. Content (%) of solids (heated residue) = Heated residue (g) × 100 / Weighted mass (g) of composition (I) The same applies to the solid content and the content of each component.
[0049] <Method for producing polymer> The method for producing the polymer (A) and the polymer (B) is not particularly limited, but may be, for example, solution polymerization, suspension polymerization, or pressure polymerization. In terms of versatility, solution polymerization carried out under normal pressure using a general organic solvent is preferred. As the solution polymerization, the following procedure may be used for production.
[0050] A solvent is charged into a reaction vessel equipped with a stirrer, a condenser, a thermometer, a dropping device, a nitrogen inlet tube, and a heating / cooling jacket, and the mixture is heated and stirred under a nitrogen stream at a temperature of about 60 to 200° C. While maintaining the same temperature, a mixture of the above-mentioned monomers, a polymerization initiator, and, if necessary, a solvent and a chain transfer agent are dropped from the dropping device, preferably so as to obtain the ratio of the structural units described above, to carry out a polymerization reaction, thereby obtaining polymer (A) or polymer (B).
[0051] The polymerization initiator is not particularly limited, and various radical polymerization initiators can be used. Specific examples include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis-4-cyanovaleric acid, benzoyl peroxide, hydrogen peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, tert-butyl peroxyoctoate, tert-butyl peroxybenzoate, potassium persulfate, sodium persulfate, etc. These radical polymerization initiators may be added to the reaction system only at the start of the reaction, or may be added to the reaction system both at the start of the reaction and during the reaction.
[0052] The amount of the polymerization initiator used in producing the polymer (A) or polymer (B) is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the total of the above-mentioned monomers (reaction raw materials).
[0053] Examples of the solvent that can be used in the production of the polymer (A) or the polymer (B) include organic solvents and water. Examples of the organic solvent include aromatic hydrocarbon solvents such as toluene, xylene, ethylbenzene, mesitylene, and coal tar naphtha; alcohol solvents such as ethanol, propanol, isopropyl alcohol, butanol, and isobutanol; ether solvents such as propylene glycol monomethyl ether and dipropylene glycol monomethyl ether; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, and cyclohexanone; and ester solvents such as ethyl acetate, butyl acetate, and propylene glycol monomethyl ether acetate.
[0054] The chain transfer agent is not particularly limited, and examples thereof include α-methylstyrene dimer, thioglycolic acid, diterpene, terpinolene, γ-terpinene; mercaptans such as tert-dodecyl mercaptan and n-dodecyl mercaptan; halides such as carbon tetrachloride, methylene chloride, bromoform and bromotrichloroethane; and secondary alcohols such as isopropanol and glycerin.
[0055] When a chain transfer agent is used in the production of the silyl ester polymer (A), the amount used is preferably 0.1 to 5 parts by mass per 100 parts by mass of the total of the above monomers (reaction raw materials).
[0056] <Medetomidine (C)> Medetomidine (C) is a compound represented by the following formula (c1), (+ / -)-4-[1-(2,3-dimethylphenyl)ethyl]-1H-imidazole, and has optical isomers, but may be only one of them or a mixture in any ratio.
[0057] [ka]
[0058] Composition (I) may contain, as a part or all of medetomidine, an adduct with an imidazolium salt, a metal, etc. In this case, an adduct with an imidazolium salt, a metal, etc. may be used as a raw material for preparing composition (I), and an adduct with an imidazolium salt, a metal, etc. may be formed in composition (I) or in an antifouling coating film formed from composition (I).
[0059] Conventional antifouling coating compositions that do not contain acrylic polymers do not have sufficient adhesion to deteriorated coating films, such as zinc acrylic resin-based antifouling coating films containing rosins, and direct coating is difficult. In response to this problem, composition (I) can significantly improve the adhesion to deteriorated coating films while maintaining dynamic antifouling properties. In addition, when an antifouling coating composition for repair is directly applied to a deteriorated coating film, the surface roughness of the formed antifouling coating film tends to be high due to the surface roughness of the deteriorated coating film, making it physically easier for aquatic organisms to attach. Since composition (I) contains medetomidine (C), it can form an antifouling coating film with excellent antifouling properties even when directly applied to the deteriorated coating film as described above. In other words, composition (I) can be said to be suitable for repair painting and repair applications for deteriorated coating films. Here, the deteriorated coating film refers to a coating film (used coating film) that has actually been immersed in seawater or freshwater for a certain period of time (for example, 30 weeks or more, preferably 50 weeks or more).
[0060] Examples of anti-fouling coating films (deteriorated coating films) to be repaired include zinc acrylic resin-based anti-fouling coating films and silyl resin-based anti-fouling coating films. In particular, anti-fouling coating films containing rosins are preferred, and zinc acrylic resin-based anti-fouling coating films containing rosins are more preferred as they better solve the adhesion problem.
[0061] The antifouling coating film containing rosins is an antifouling coating film containing rosins in an amount of usually 0.5 to 40% by mass, preferably 1 to 30% by mass, more preferably 1.5 to 15% by mass, from the viewpoint of more effectively achieving the effects of the present invention. The antifouling coating film is formed, for example, from an antifouling paint composition containing rosins in an amount of usually 0.5 to 40% by mass, preferably 1 to 30% by mass, more preferably 1.5 to 15% by mass, based on 100% by mass of the solid content of the composition. Examples of rosins include those listed below as rosins (E1).
[0062] The content of medetomidine (C) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and preferably 2% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.15% by mass or less, based on 100% by mass of the solid content of the composition (I). The content of medetomidine (C) in the composition (I) is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less, and particularly preferably 1 part by mass or less, based on 100 parts by mass of the total of the silyl ester polymer (A) and the acrylic polymer (B). When the content of medetomidine (C) is in this range, the antifouling coating film formed from the composition (I) exhibits better antifouling properties. Furthermore, when the content of medetomidine (C) is in a particularly preferred range, the composition (I) exhibits better storage stability.
[0063] <Copper oxide (D)> The antifouling coating composition containing a silyl ester polymer (A) and medetomidine (C) can improve the dynamic antifouling properties against aquatic organisms such as slime, algae such as Ulva, and other plant species by containing cuprous oxide (D).
[0064] The content of the cuprous oxide (D) is more than 0 mass% and not more than 55 mass%, preferably 10 to 53 mass%, more preferably 20 to 52 mass%, of the solid content of the antifouling coating composition. When the content of the cuprous oxide (D) is equal to or more than the lower limit, the dynamic antifouling properties of the antifouling coating film formed are improved, and when it is equal to or less than the upper limit, the composition (I) has excellent long-term storage stability and the dynamic antifouling properties of the antifouling coating film formed are improved.
[0065] Although the mechanism of action of the above-mentioned effect is not clear, for example, in an antifouling coating composition containing a silyl ester polymer (A), medetomidine (C) and a specific amount of cuprous oxide (D), it is presumed that the interaction between these components causes the silyl ester polymer (A) to have a significant increase in molecular weight, resulting in a high viscosity coating composition. However, since the amount of cuprous oxide (D) in the antifouling coating composition (I) of the present invention is less than a specific amount, it is presumed that this increase in viscosity is suppressed and long-term storage stability is improved. Similarly, although the mechanism of action is not clear, it is presumed that the interaction between these components causes the antifouling coating composition (I) containing a silyl ester polymer (A) and a polymer (B) and a specific amount or less of cuprous oxide (D) to moderately increase the wear rate of the coating film, resulting in improved dynamic antifouling properties against aquatic organisms of plant species.
[0066] The cuprous oxide (D) preferably has an average particle size of about 1 to 30 μm, and more preferably includes one having an average particle size of 2 to 10 μm from the viewpoint of improving the antifouling properties and water resistance of the antifouling coating film to be formed. The cuprous oxide (D) is preferably surface-treated with glycerin, stearic acid, lauric acid, sucrose, lecithin, mineral oil, or the like, from the viewpoint of long-term stability during storage of the composition (I).
[0067] As such cuprous oxide (D), commercially available products can be used, such as NC-301 (average particle size: 2 to 4 μm) and NC-803 (average particle size: 6 to 10 μm) manufactured by NC Tech Co., Ltd., and Red Copp97N Premium, Purple Copp, and LoLoTint97 manufactured by AMERICAN CHEMET Co., Ltd.
[0068] <Monocarboxylic acid compound (E)> The composition (I) preferably contains a monocarboxylic acid compound (E) from the viewpoints of not only improving the antifouling properties but also adjusting the wear rate of the coating film. Examples of the monocarboxylic acid compound (E) include aliphatic or alicyclic monocarboxylic acids, their monocarboxylic acid derivatives, and their metal salts. Examples of the monocarboxylic acid derivatives include esters and amides of monocarboxylic acids. Examples of the metal salts include zinc salts, copper salts, aluminum salts, magnesium salts, calcium salts, and barium salts. Specific examples of monocarboxylic acids include rosins (E1), naphthenic acid, cycloalkenyl carboxylic acids, bicycloalkenyl carboxylic acids, trimethylisobutenylcyclohexene carboxylic acids, isononanoic acid, neodecanoic acid, versatic acid, stearic acid, hydroxystearic acid, palmitic acid, oleic acid, linoleic acid, linolenic acid, pimaric acid, abietic acid, and neoabietic acid. Among these, rosins (E1) are preferred from the viewpoint of being able to easily obtain a coating film that is excellent in crack resistance and long-term antifouling properties.
[0069] Examples of the rosins (E1) include rosins such as gum rosin, wood rosin, and tall oil rosin; rosin derivatives such as hydrogenated rosin, disproportionated rosin, and rosin metal salts; and pine tar. The monocarboxylic acid compound (E) can be used alone or in combination of two or more. In the composition (I), the mass ratio of the monocarboxylic acid compound (E) to the total of the silyl ester polymer (A) and the acrylic polymer (B) (total mass of polymer (A) and polymer (B) / mass of monocarboxylic acid compound (E)) is preferably 0.5 or more, more preferably 0.7 or more, and is preferably 5 or less, more preferably 4 or less.
[0070] In particular, the mass ratio of the rosins (E1) to the total of the silyl ester polymer (A) and the acrylic polymer (B) in the composition (I) (total mass of the polymer (A) and the polymer (B) / mass of the rosins (E1)) is preferably 0.7 to 4, more preferably 0.7 to 3.5, and even more preferably 0.7 to 3. In one embodiment, this mass ratio is more than 1.5 and 3.5 or less. In such an embodiment, the adhesion, dynamic antifouling property, and crack resistance of the antifouling coating film formed from the composition (I) to deteriorated coating films such as antifouling coating films containing rosins tend to be further improved.
[0071] That is, when the mass ratio is 4 or less, the adhesion to deteriorated coating films and the dynamic antifouling properties tend to be better than when it exceeds 4, and when the mass ratio is 0.7 or more, the adhesion to deteriorated coating films and the crack resistance tend to be better than when it is below 0.7. Therefore, the composition (I) that satisfies the above mass ratio requirement can be directly applied to the deteriorated coating films without using, for example, a binder, and is particularly suitable for repair painting and maintenance of deteriorated coating films.
[0072] <Other components> In addition to the above-mentioned components, composition (I) may further contain one or more of copper and / or a copper compound, an organic antifouling agent other than medetomidine (C), a colorant, an extender pigment, a thixotropic agent, a dehydrating agent, a plasticizer, a resin other than the polymer (A) and the polymer (B), and a solvent. Each of the components explained below can be used alone or in combination of two or more.
[0073] ≪Copper and / or copper compound≫ Composition (I) may contain copper and / or a copper compound as an antifouling agent from the viewpoint of further improving antifouling properties against aquatic organisms of animal species. Examples of copper include copper powder. Examples of copper compounds include copper thiocyanate and cupronickel, with copper thiocyanate being preferred. Cuprous oxide (D) is not classified as a copper compound, and copper pyrithione is not classified as a copper compound but as an organic antifouling agent as described below.
[0074] The content of copper and / or a copper compound is preferably 0.1 to 45 mass %, more preferably 1 to 35 mass %, relative to 100 mass % of the total solid content of the composition (I).
[0075] ≪Organic antifouling agent≫ The composition (I) preferably contains an organic antifouling agent other than medetomidine (C) as the antifouling agent. The organic antifouling agent is a component that further improves the antifouling properties of the antifouling coating film.
[0076] Examples of organic antifouling agents include metal pyrithiones such as copper pyrithione and zinc pyrithione, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile, pyridinetriphenylborane, 4-isopropylpyridinediphenylmethylborane, N,N-dimethyl-N'-(3,4-dichlorophenyl)urea, N-(2,4,6-trichlorophenyl)maleimide, 2-methylthio-4-tert-butylamino-6-cyclopropylamino-1,3,5-triazine, 2,4,5,6-tetrachlorophenyl ... Examples of suitable thiol compounds include thiol, bis(dimethyldithiocarbamoyl)zinc ethylene bisdithiocarbamate, chloromethyl-n-octyl disulfide, N',N'-dimethyl-N-phenyl-(N-fluorodichloromethylthio)sulfamide, N',N'-dimethyl-N-tolyl-(N-fluorodichloromethylthio)sulfamide, tetraalkylthiuram disulfide, zinc dimethyl dithiocarbamate, zinc ethylene bisdithiocarbamate, 2,3-dichloro-N-(2',6'-diethylphenyl)maleimide, and 2,3-dichloro-N-(2'-ethyl-6'-methylphenyl)maleimide. Among these, metal pyrithiones such as copper pyrithione and zinc pyrithione, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile, and bisdimethyldithiocarbamoylzinc ethylenebisdithiocarbamate are preferred, and copper pyrithione and 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one are more preferred.
[0077] The content of the organic antifouling agent other than medetomidine (C) is preferably 0.05 to 20 mass %, more preferably 0.1 to 10 mass %, relative to 100 mass % of the total amount of the solids in the composition (I).
[0078] ≪Colorant≫ As the colorant, various organic and inorganic pigments and dyes known in the art can be used. Examples of organic pigments include naphthol red and phthalocyanine blue. Examples of inorganic pigments include carbon black, red iron oxide, baryte powder, titanium white (titanium oxide), and yellow iron oxide. It is preferable that the composition (I) contains a colorant, since the hue of the antifouling coating film obtained from the composition can be adjusted as desired. The content of the colorant is preferably from 0.01 to 50 mass %, and more preferably from 0.01 to 30 mass %, relative to 100 mass % of the total solid content of the composition (I).
[0079] ≪Extender pigment≫ Examples of the extender pigment include zinc oxide, talc, silica, mica, clay, potassium feldspar, calcium carbonate, kaolin, alumina white, white carbon, aluminum hydroxide, magnesium carbonate, barium carbonate, barium sulfate, and zinc sulfide. Among these, zinc oxide, talc, silica, mica, clay, calcium carbonate, kaolin, barium sulfate, and potassium feldspar are preferred.
[0080] From the viewpoint of improving the coating film properties such as crack resistance of the resulting antifouling coating film, composition (I) preferably contains an extender pigment, more preferably talc. The content of the extender pigment is preferably 0.1 to 50 mass %, more preferably 1 to 40 mass %, relative to 100 mass % of the total solid content of the composition (I). The content of talc is preferably 2 to 17% by mass relative to 100% by mass of the total amount of solids in the composition (I), from the viewpoint of further improving coating film properties such as crack resistance.
[0081] ≪Thickener≫ The thixotropic agent is a component that contributes to preventing the paint from sagging and settling. Examples of thixotropic agents (anti-sagging agents, anti-settling agents) include salts selected from the group consisting of organic bentonite, amine salts of Al, Ca or Zn, stearate salts, lecithin salts and alkylsulfonate salts; waxes selected from the group consisting of polyethylene wax, oxidized polyethylene wax, amide wax, hydrogenated castor oil wax and polyamide wax; and synthetic finely powdered silica.
[0082] The thixotropic agent is used for the purposes of preventing precipitation of solid materials such as copper and / or copper compounds, organic antifouling agents, colorants, extender pigments, dehydrating agents, etc. during storage of the antifouling coating composition, and of improving coating workability during coating. The content of the thixotropic agent is preferably 0.1 to 20 mass %, more preferably 0.1 to 10 mass %, relative to 100 mass % of the total amount of the solids in the composition (I).
[0083] ≪Dehydrating agent≫ Examples of the dehydrating agent include inorganic dehydrating agents and organic dehydrating agents, and examples of the inorganic dehydrating agent include synthetic zeolite, anhydrous gypsum, and hemihydrate gypsum, and examples of the organic dehydrating agent include alkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetrabutoxysilane, tetraphenoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, and trimethylethoxysilane, or polyalkoxysilanes which are condensates thereof, and orthoformic acid alkyl esters such as methyl orthoformate and ethyl orthoformate. The dehydrating agent is used for the purpose of preventing gelation due to decomposition of hydrolyzable resins caused by moisture generated during production and / or storage of the antifouling coating composition. The content of the dehydrating agent is preferably 0.01 to 10 mass %, more preferably 0.1 to 5 mass %, relative to 100 mass % of the total solid content of the composition (I).
[0084] ≪Plasticizer≫ Examples of the plasticizer include n-paraffin, chlorinated paraffin, petroleum resin, ketone resin, tricresyl phosphate, polyvinyl ethyl ether, and dialkyl phthalate, and among these, chlorinated paraffin, petroleum resin, and ketone resin are preferred. When the composition (I) contains a plasticizer, it is preferred in that the crack resistance and water resistance of the antifouling coating film obtained from the composition are further improved.
[0085] The chlorinated paraffin may have either a linear or branched molecular structure, and may be in a liquid state or a solid (powder state) under room temperature conditions. The average number of carbon atoms in one molecule of the chlorinated paraffin is preferably 8 to 30, more preferably 10 to 26. An antifouling coating composition containing such chlorinated paraffin can form an antifouling coating film with less cracking and peeling. When the average number of carbon atoms is 8 or more, the effect of suppressing the occurrence of cracks is high, while when the average number of carbon atoms is 30 or less, it is preferable since the antifouling property is not suppressed.
[0086] The viscosity (unit: poise, measured at 25°C) of the chlorinated paraffin is preferably 1 or more, more preferably 1.2 or more, and the specific gravity (25°C) is preferably 1.05 to 1.80 g / cm 3 , more preferably 1.10 to 1.70 g / cm 3 It is.
[0087] Examples of petroleum resins include C5, C9, styrene, and dicyclopentadiene resins, as well as hydrogenated products thereof. The content of the plasticizer is preferably 0.01 to 10 mass %, more preferably 0.1 to 5 mass %, relative to 100 mass % of the total solid content of the composition (I).
[0088] ≪Resins other than polymer (A) and polymer (B)≫ The composition (I) may contain resins other than the above-mentioned polymer (A) and polymer (B). Examples of the resins include water-insoluble or poorly water-soluble resins such as polyester resin, unsaturated polyester resin, fluororesin, polybutene resin, polyurethane resin, epoxy resin, polyamide resin, vinyl resin (vinyl chloride copolymer, ethylene-vinyl acetate copolymer, etc.), styrene-butadiene copolymer resin, alkyd resin, coumarone resin, terpene phenol resin, silicone rubber, and chlorinated rubber. The content of the resins is, for example, 0.01 to 100 parts by mass relative to 100 parts by mass in total of the polymer (A) and the polymer (B).
[0089] ≪Solvent≫ Composition (I) may contain a solvent such as water or an organic solvent, if necessary, in order to improve the dispersibility of each component or adjust the viscosity of the composition. The solvent may be the solvent used when preparing the polymer (A) or the polymer (B), or may be a solvent added separately when preparing the antifouling coating composition by mixing the polymer (A) and the polymer (B) with other components as necessary. The solvent is preferably an organic solvent. Examples of the organic solvent include the organic solvents described in the section <Method of producing a polymer>.
[0090] When the composition (I) contains a solvent, the content is determined by the desired viscosity according to the application form of the coating composition. The content of the solvent in the composition (I) is preferably 5 to 50 mass%, more preferably 10 to 40 mass%. If the content of the solvent is too high, problems such as a decrease in anti-sagging properties may occur.
[0091] <Method for producing antifouling paint composition> Composition (I) can be produced by appropriately utilizing a known method, except for using polymer (A), polymer (B), medetomidine (C), and a specific amount of cuprous oxide (D). For example, composition (I) may be produced by adding polymer (A), polymer (B), medetomidine (C), a specific amount of cuprous oxide (D), and, if necessary, monocarboxylic acid compound (E) and / or other components to a stirring vessel all at once or in any order, mixing each component by known stirring / mixing means, and dispersing or dissolving in a solvent.
[0092] Examples of the stirring and mixing means include a paint shaker, a high-speed disperser, a sand grind mill, a basket mill, a ball mill, a three-roll mill, a Ross mixer, a planetary mixer, and a universal Shinagawa mixer.
[0093] [Use of antifouling paint composition] The antifouling coating film of this embodiment (hereinafter also referred to as "antifouling coating film (J)") is formed from the composition (I). The substrate with the antifouling coating film of this embodiment (hereinafter also referred to as "antifouling substrate (K)") has a substrate and an antifouling coating film (J) provided on the surface of the substrate.
[0094] The method for producing the antifouling substrate (K) comprises a step of coating or impregnating a substrate (object, coated object) with the composition (I), and, when the composition (I) contains a solvent, further comprises a step of drying the coated or impregnated body obtained by coating or impregnating the substrate.
[0095] For application, known methods such as air spray, airless spray, brush, roller, etc. can be used. The composition (I) applied or impregnated by the above-mentioned method can be dried by leaving it for about 1 to 14 days, more preferably about 1 to 7 days, and more preferably about 1 to 5 days under conditions of -5 to 30°C, to obtain an antifouling coating film (J). The composition (I) may be dried while blowing air under heating.
[0096] Alternatively, the antifouling substrate (K) can be produced by forming an antifouling coating film (J) from the composition (I) on the surface of a temporary substrate, peeling the antifouling coating film (J) from the temporary substrate, and attaching it to the substrate to be antifouled. In this case, the antifouling coating film (J) may be attached to the substrate via an adhesive layer.
[0097] The surface of the substrate may be primer-treated, and may have a layer formed from various resin-based paints such as epoxy resin-based paints, vinyl resin-based paints, acrylic resin-based paints, and urethane resin-based paints on the surface. The substrate may also be an antifouling substrate having an antifouling coating film, and may be an antifouling substrate having a deteriorated coating film of an antifouling coating film such as a zinc acrylic resin-based antifouling coating film containing rosins. In this case, the surface of the substrate on which the antifouling coating film (J) is provided means the surface after primer treatment, the surface of the layer formed from the above-mentioned paint, and the surface of the antifouling coating film.
[0098] Although the substrate is not particularly limited, the composition (I) is preferably used for preventing the substrate from fouling for a long period of time in a wide range of industrial fields such as ships, fisheries, and underwater structures. For this reason, examples of the substrate include ships (e.g., large steel ships such as container ships and tankers, hull shells such as fishing boats, FRP ships, wooden ships, and yachts, and both new ships and repaired ships are included), underwater structures (e.g., oil pipelines, water conveyance pipes, circulating water pipes, water supply and drainage outlets of factories and thermal and nuclear power plants, undersea cables, seawater utilization equipment (seawater pumps, etc.), megafloats, coastal roads, undersea tunnels, port facilities, various underwater civil engineering structures in canals and waterways, etc.), fishing materials (e.g., ropes, fishing nets, fishing gear, floats, buoys), water supply and drainage pipes for seawater in factories and thermal and nuclear power plants, diver suits, underwater goggles, oxygen cylinders, swimsuits, torpedoes, etc. Among these, ships, underwater structures, fishing equipment, and water supply and drainage pipes are preferred, ships and underwater structures are more preferred, and ships are particularly preferred.
[0099] In producing the antifouling substrate (K), when the substrate is a fishing net or a steel plate, the composition (I) may be directly applied to the substrate surface, when the substrate is a fishing net, the composition (I) may be impregnated into the substrate surface, and when the substrate is a steel plate, a base material such as a rust inhibitor or a primer may be applied to the substrate surface in advance to form a base layer, and then the composition (I) may be applied to the surface of the base layer. In addition, for the purpose of repair, an antifouling coating film (J) or a conventional antifouling coating film (e.g., a deteriorated coating film of a zinc acrylic resin-based antifouling coating film containing rosins) may be further formed on the surface of the substrate, such as a steel plate having a deteriorated antifouling coating film (e.g., a deteriorated coating film of a zinc acrylic resin-based antifouling coating film containing rosins).
[0100] The thickness of the antifouling coating film (J) is not particularly limited, but is, for example, about 30 to 1000 μm. When the antifouling coating film (J) is formed by applying the composition (I) to a substrate, the thickness of the antifouling coating film (J) formed by one application (if the composition (I) contains a solvent, the thickness of the coating film after the solvent is removed) is preferably 10 to 300 μm, more preferably 30 to 200 μm, and may be applied once or multiple times.
[0101] A ship having the antifouling coating film (J) can prevent a decrease in ship speed and an increase in fuel consumption because it can prevent the attachment of aquatic organisms. An underwater structure having the antifouling coating film (J) can maintain the function of the underwater structure for a long period of time because it can prevent the attachment of aquatic organisms over a long period of time. A fishing net having the antifouling coating film (J) can prevent clogging of the mesh because it can prevent the attachment of aquatic organisms. Furthermore, a water supply and drainage pipe having the antifouling coating film (J) on its inner surface can prevent clogging of the water supply and drainage pipe and a decrease in flow speed because it can prevent the attachment and proliferation of aquatic organisms. EXAMPLES
[0102] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples and comparative examples, "parts" refers to "parts by mass".
[0103] [Measurement conditions] The polymer was subjected to gel permeation chromatography (GPC) measurement, and the polymer solution was subjected to measurement of the heating residue content. The measurement conditions were as follows:
[0104] <GPC measurement conditions> Equipment: "HLC-8320GPC" (Tosoh Corporation) Column: "TSKgel guardcolumn SuperMP(HZ)-M+TSKgel SuperMultiporeHZ-M+TSKgel SuperMultiporeHZ-M" (all manufactured by Tosoh Corporation) Eluent: tetrahydrofuran (THF) Flow rate: 0.35ml / min Detector: RI Column thermostat temperature: 40℃ Calibration curve: Standard polystyrene and styrene monomer Sample preparation method: The polymer solution obtained in each production example was diluted with THF, and then filtered through a membrane filter to obtain a filtrate, which was used as a GPC measurement sample.
[0105] <Measurement conditions for content of solid content (heating residue)> The polymer solution was weighed out into a metal test dish of known mass and spread evenly on the bottom. It was then heated in a hot air dryer at 105-110°C for 3 hours to remove the volatiles. After removing it and cooling it to room temperature (e.g. 23°C), the mass of the resulting non-volatiles (heated residue) was measured and the solid content was calculated using the following formula. Solid content (heated residue) content (%) = heated residue (g) × 100 / weight of polymer solution (g)
[0106] [Production example of polymer] [Production example 1] Production of solution of silyl ester polymer (A) A reaction vessel equipped with a stirrer, a condenser, a thermometer, a nitrogen inlet tube and a dropping device was charged with 43 parts of xylene and 10 parts of triisopropylsilyl methacrylate, and heated and stirred under a nitrogen atmosphere until the liquid temperature reached 80°C. While maintaining the same conditions, a mixture of monomers (50 parts of triisopropylsilyl methacrylate, 25 parts of 2-methoxyethyl methacrylate, 10 parts of methyl methacrylate, 5 parts of n-butyl acrylate) and a polymerization initiator (1.35 parts of 2,2'-azobis(isobutyronitrile)) was dropped into the reaction vessel over 2 hours from the dropping device. Next, the mixture was heated and stirred at the same temperature for 1 hour and at a liquid temperature of 88°C for 1 hour, after which the liquid temperature was raised to 95°C. While maintaining the same temperature, 0.1 parts of 2,2'-azobis(isobutyronitrile) was added a total of 4 times at 30 minute intervals, and then the liquid temperature was raised to 105°C. Heating and stirring were continued at the same temperature for 30 minutes, and then 23.7 parts of xylene was added to the reaction vessel to obtain a solution of a silyl ester polymer (A-1).
[0107] The same procedure as above was carried out except that the monomers were changed as shown in Table 1, to obtain a solution of a silyl ester polymer (A-2) and a solution of a silyl ester polymer (cA-1) for comparison.
[0108] [Production example 2] Production of solution of acrylic polymer (B) A reaction vessel equipped with a stirrer, a condenser, a thermometer, a nitrogen inlet tube and a dropping device was charged with 66.7 parts of xylene, and the mixture was heated and stirred under a nitrogen atmosphere until the liquid temperature reached 110° C. From the dropping device, a mixture of monomers (50 parts of styrene, 15 parts of methyl methacrylate, 25 parts of n-butyl acrylate, 10 parts of glycidyl methacrylate) and a polymerization initiator (1.5 parts of 2,2'-azobis (2-methylbutyronitrile), 1 part of tert-butyl peroxybenzoate) was dropped into the reaction vessel over 3 hours while maintaining the same conditions, and then the mixture was heated and stirred for 1 hour at the same temperature, 1 hour at 120° C., and 1 hour at 130° C., after which 7.16 parts of xylene was added to the reaction vessel to obtain a solution of an acrylic polymer (B-1).
[0109] The same procedure as above was carried out except that the monomers were changed as shown in Table 2, to obtain solutions of acrylic polymers (B-2) to (B-4) and solutions of acrylic polymers (cB-1) to (cB-2) for comparison.
[0110] The weight average molecular weights of these silyl ester polymers and acrylic polymers, and the solid content (heating residue) of these solutions are shown in Tables 1 and 2. The numerical values for monomers indicate the blending amounts (parts by mass).
[0111] [Table 1]
[0112] [Table 2]
[0113] [Preparation of antifouling paint composition] [Example 1] An antifouling coating composition was prepared as follows. 0.1 parts of medetomidine (Selektope®) and 0.9 parts of methoxypropanol (PGM) were added to a plastic container and mixed using a paint shaker until the medetomidine was uniformly dissolved. 14.0 parts of xylene and 6.5 parts of gum rosin (China Gum Rosin WW) were added to the resulting solution and mixed again using a paint shaker until the rosin was uniformly dissolved. Thereafter, 12.0 parts of a solution of a silyl ester polymer (A-1) and 5.0 parts of a solution of an acrylic polymer (B-1) were added to the resulting solution, and the mixture was stirred until uniformly mixed. Next, 10 parts of zinc oxide (three types of zinc oxide), 37 parts of cuprous oxide (NC-301), 2.0 parts of titanium oxide (Typique R-930), 1.5 parts of red oxide (TODA COLOR NM-50), 6.0 parts of talc (FC-1), 1.0 parts of copper pyrithione (Copper Omadine Powder), 2.0 parts of oxidized polyethylene wax (Disparlon 4200-20X), and 0.5 parts of tetraethoxysilane (ethyl silicate 28) were added, and 200 parts of glass beads were added and the mixture was stirred and dispersed for 1 hour using a paint shaker. To the obtained dispersion, 1.5 parts of amide wax (Disparlon A630-20X) was added and the mixture was stirred for 20 minutes to disperse it, and then the glass beads were removed from the mixture using an 80 mesh filter to prepare an antifouling coating composition.
[0114] [Examples 2 to 19, Comparative examples 1 to 7] Antifouling coating compositions were prepared in the same manner as in Example 1, except that the types and amounts of each component were changed as shown in Table 3.
[0115] [Physical property evaluation of antifouling paint composition] The physical properties of the coating films formed using the antifouling coating compositions obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Table 3.
[0116] <Crack resistance> An epoxy-based anticorrosive paint (product name "Banno 500", manufactured by Chugoku Toryo Co., Ltd., hereinafter referred to as "Epoxy 1") was applied to a sandblasted steel plate having dimensions of 300 mm length, 100 mm width, and 2.3 mm thickness using an air spray so that the dry film thickness was 150 μm, and the coating was dried at 23° C. for one week to form a cured coating film. Next, an epoxy-based binder paint (product name "Banno 500N", manufactured by Chugoku Toryo Co., Ltd., hereinafter referred to as "Epoxy 2") was applied to the cured coating film of Epoxy 1 using an air spray so that the dry film thickness was 100 μm, and the coating was dried at 23° C. for 24 hours.
[0117] Next, each composition prepared in the Examples and Comparative Examples was applied to the surface of the cured coating film of Epoxy 2 to a dry film thickness of 200 μm, and then dried at 23° C. for 7 days to form an antifouling coating film, and a crack resistance test panel was prepared.
[0118] The crack resistance test panels thus prepared were immersed in natural seawater heated to 50°C for six months, and the presence or absence of cracks (area basis) was confirmed. Evaluation criteria (Evaluation based on the ratio of crack area to the total surface area of the coating film. 4 or above is a pass.) 5: No cracks observed. 4: Cracks are observed in less than 2% of the area. 3: Cracks are observed in 2% or more but less than 30% of the area. 2: Cracks are observed in 30% to 80% of the area. 1: Cracks are observed in more than 80% of the area.
[0119] <Adhesion to deteriorated coating film> Epoxy 1 was applied to a sandblasted steel plate measuring 300 mm in length, 100 mm in width, and 3.2 mm in thickness in the same manner as in the crack resistance test, so that the dry film thickness was 150 μm, and epoxy 2 was applied to a dry film thickness of 100 μm. On the surface of the cured coating film formed from epoxy 2, rosin-containing zinc acrylic antifouling paint 1 (rosin content is 6% by mass relative to 100% by mass of the solid content of the antifouling paint) was applied to a dry film thickness of 200 μm, and dried at 23° C. for 7 days. The plate was immersed in seawater on a test raft for one year. The plate was pulled up and subjected to a pressure of 80 kgf / cm 2 After drying, the antifouling coating composition prepared in the examples or comparative examples was applied to the surface of the deteriorated coating film 1 formed from the zinc acrylic antifouling coating 1 so that the dry film thickness was 200 μm, and the antifouling coating film was formed by drying at 23 ° C for 7 days, and an adhesion test plate 1 for the deteriorated coating film 1 was prepared. The plate was immersed in natural seawater at 23 ° C for 10 months, and then dried at 23 ° C for 1 day. Thereafter, a checkerboard peel test (cross-cut method) was carried out on 25 squares of 4 mm × 4 mm basically in accordance with JIS K 5600-5-6 (1999) regardless of the dry film thickness, and the adhesion was evaluated based on the area of the remaining coating film relative to the test area.
[0120] Evaluation criteria (4 or above is pass) 5: Peeling area less than 5% 4: Peeling area is 5% or more but less than 10% 3: Peeling area is 10% or more but less than 40% 2: Peeling area is 40% or more but less than 70% 1: Peeling area is 70% or more but less than 100%
[0121] Instead of the zinc acrylic antifouling paint 1, the deteriorated coating film was replaced with a zinc acrylic antifouling paint 2 not containing rosin, a silyl antifouling paint 3 containing rosin (the rosin content was 7% by mass relative to 100% by mass of the solid content of the antifouling paint 3), and a silyl antifouling paint 4 containing rosin (the rosin content was 2% by mass relative to 100% by mass of the solid content of the antifouling paint 4). Test plates were prepared in the same manner as the zinc acrylic antifouling paint 1. These test plates were immersed in seawater for one year on a test raft, and then washed with water in the same manner as above. The deteriorated coating film 2 formed from the zinc acrylic antifouling paint 2, the deteriorated coating film 3 formed from the silyl antifouling paint 3, and the deteriorated coating film 4 formed from the silyl antifouling paint 4 were coated with the antifouling paint composition prepared in the examples or comparative examples to a dry film thickness of 200 μm, and dried at 23 ° C. for 7 days to form an antifouling coating film, and adhesion test plates 2 to 4 for the deteriorated coating films 2 to 4 were prepared. These plates were then immersed in artificial seawater at 40° C. for 6 months, and the adhesion was evaluated in the same manner as above.
[0122] <Dynamic antifouling property> Dynamic antifouling test panels were prepared using sandblasted steel panels measuring 150 mm in length, 70 mm in width, and 1.6 mm in thickness, following the same procedure as for the crack resistance test panels. The obtained test panels were immersed in seawater off the coast of Kure, Hiroshima Prefecture, and a rotating rotor was used to generate a water current of about 15 knots per hour. The water current was applied to the antifouling coating surface of the test panels for 12 months, and the ratio of the area of the area where aquatic organisms were attached to the antifouling coating surface of the test panels was evaluated by visual observation.
[0123] Evaluation criteria (4 or above is pass) 5: No adhesions observed. 4: Slime adhesion is observed in less than 10% of the area. 3: Slime adhesion is observed in areas between 10% and 60%. 2: Slime adhesion is observed in areas between 60% and 90%. 1: Slime adhesion is observed in more than 90% of the area.
[0124] [Table 3-1] [Table 3-2]
[0125] [Storage stability evaluation of antifouling paint composition] The storage stability of the antifouling coating compositions obtained in the Examples and Comparative Examples was evaluated as follows. The results are shown in Table 4.
[0126] <Storage stability> The initial viscosity of each of the antifouling coating compositions of some of the Examples and Comparative Examples prepared by the above method was measured one day after preparation, and then stored at 50° C. for two months. The viscosity of each composition after storage was measured, and the viscosity increase rate was calculated using the following formula. If the viscosity increase rate is less than 20%, it is considered to be acceptable. In addition, antifouling coating compositions with a viscosity increase rate of 20% or more cause problems such as a marked decrease in coating workability or an increase in the amount of organic solvent required for dilution, which increases the environmental load. Viscosity increase rate = (viscosity after storage - initial viscosity) / initial viscosity x 100
[0127] [Table 4]
[0128] Details of the components used in the examples and comparative examples are as follows. [Table 5]
Claims
1. A silyl ester polymer (A) having a structural unit (a-1) derived from a polymerizable monomer (a1) represented by formula (a1), An acrylic polymer (B) having a structural unit (b-1) derived from glycidyl (meth)acrylate; Medetomidine (C), Cuprous oxide (D) An antifouling coating composition comprising: An antifouling coating composition, wherein the content of the cuprous oxide (D) is more than 0 mass% and 55 mass% or less in the solid content of the antifouling coating composition. R 1 -CH=C(CH 3 )-COO-(SiR 2 R 3 O) n -SiR 4 R 5 R 6 …(a1) [In formula (a1), R 2 ~R 6 are each independently a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom. n is an integer of 0 or 1 or more. 1 is a hydrogen atom or R 7 is a group represented by —O—C(═O)—, and R 7 represents a hydrogen atom, a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom, or R 8 R 9 R 10 is a silyl group represented by Si-, R 8 , R 9 and R 10 each independently represents a monovalent organic group having 1 to 20 carbon atoms which may have a heteroatom.]
2. The antifouling coating composition according to claim 1, further comprising a monocarboxylic acid compound (E).
3. 3. The antifouling coating composition according to claim 2, wherein the monocarboxylic acid compound (E) is a rosin (E1).
4. The antifouling coating composition according to claim 3, wherein a mass ratio of the rosin (E1) to the total of the silyl ester polymer (A) and the acrylic polymer (B) (total mass of polymer (A) and polymer (B) / mass of rosin (E1)) is 0.7 to 4.
5. The antifouling coating composition according to any one of claims 1 to 4, further comprising talc, the talc content being 2 to 17 mass% of the solid content of the antifouling coating composition.
6. The antifouling coating composition according to any one of claims 1 to 5, which is used for repairing a deteriorated antifouling coating film.
7. An antifouling coating film formed from the antifouling coating composition according to any one of claims 1 to 6.
8. A substrate; The antifouling coating film according to claim 7 provided on the surface of the substrate. A substrate having an antifouling coating film.
9. The substrate with an antifouling coating film according to claim 8, wherein the substrate is at least one selected from ships, underwater structures, fishing materials, and water supply and drainage pipes.
10. A method for producing a substrate having an antifouling coating film, comprising a step of coating or impregnating a substrate with the antifouling coating composition according to any one of claims 1 to 6.
Citation Information
Patent Citations
Antifouling coating composition, antifouling coating film, antifouling base, and method of manufacturing antifouling base
EP3385345A1
Antifouling coating material composition
JP2001172548A
Antifouling composition
JP2019535868A
Antifouling paint composition, antifouling paint film, antifouling substrate, and method for manufacturing antifouling substrate
WO2014175246A1
Antifouling coating composition
WO2019198676A1